Stress Analysis Of Reinforced Earth Bridge Abutment ? Synopsis - S. D. Zhang (Deep Foundations Institute, 2010)
The first reinforced earth railway bridge abutment in China has been successfully constructed of September, 1985 under the supervision of the Reinforced Earth Researth Group of Shanghai Institute of Railway Technology. In order to verify the reliability of the designed structure and its behaviuors, the 1:10 reduced scale model tests in laboratory and field tests on the actual structure during construction were proceeded. Various loads of different positions were charged, the vertical and lateral earth pressure in the filling soil, the stresses developed in the reinforcements, and the deformations of the models or the actual structure were recorded in those tests. The behaviors recorded are presented and discussed in this paper.